Thiophenecarboxylate Suppressor of Cyclic Nucleotides Discovered in a Small-Molecule Screen Blocks Toxin-Induced Intestinal Fluid Secretion - Tradtrantip, Lukmanee; Yangthara, Buranee; Padmawar, Prashant; Morrison, Christopher; Verkman, A.S. (Molecular pharmacology, 2009)
We carried out a “pathway” screen of 50,000 small molecules to identify novel modulators of cAMP signaling. One class of compounds, the 2-(acylamino)-3-thiophenecarboxylates, strongly suppressed cAMP and cGMP in multiple cell lines in response to different agonists acting on G-protein-coupled receptors, adenylyl cyclase, and guanylyl cyclase. The best compounds from structure-activity analysis of 124 analogs, including several synthesized chiral analogs, had and IC50 of <5 μM for suppression of agonist-induced cAMP and cGMP elevation. Measurements of cAMP, cGMP, and downstream signaling in response to various activators/inhibitors suggested that the 2-(acylamino)-3-thiophenecarboxylates function as nonselective phosphodiesterase activators, although it was not determined whether their action on phosphodiesterases is direct or indirect. The 2-(acylamino)-3-thiophenecarboxylates suppressed CFTR-mediated Cl- current in T84 colonic cells in response to cholera and Escherichia coli (STa) toxins, and prevented intestinal fluid accumulation in a closed-loop mouse model of secretory diarrhea. They also prevented cyst growth in an in vitro renal epithelial cell model of polycystic kidney disease. The 2-(acylamino)-3-thiophenecarboxylates represent the first small-molecule cyclic nucleotide suppressors, whose potential therapeutic indications include secretory diarrheas, polycystic kidney disease, and growth inhibition of cAMP-dependent tumors.